2021
DOI: 10.1016/j.ufug.2021.127340
|View full text |Cite
|
Sign up to set email alerts
|

Addressing psychosocial issues caused by the COVID-19 lockdown: Can urban greeneries help?

Abstract: The Coronavirus disease-2019 (COVID-19) pandemic has affected over 200 countries, forcing governments to impose lockdowns to contain the spread of the disease. Although effective in reducing infection rates, the lockdowns have also resulted in a severe negative impact on mental health throughout the world; Setting the foundation for mental illnesses to become the next “silent” pandemic. This study attempts to determine a self-care method of ensuring mental health during the COVID-19 pandemic, especially for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…These results suggest that people intentionally go outdoors and visit greenspaces for restorative purposes. Indeed, there are now insights explicitly for the pandemic suggesting that nature exercise and nature therapy in urban greenspaces can help reduce stress, anxiety and depressive symptoms (Sundara Rajoo et al, 2021). Furthermore, there is evidence that even brief outdoor experiences in green and blue spaces or having green window views during the strictest lockdown periods provide mental health benefits (Pouso et al, 2021; Soga, Evans, Tsuchiya, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that people intentionally go outdoors and visit greenspaces for restorative purposes. Indeed, there are now insights explicitly for the pandemic suggesting that nature exercise and nature therapy in urban greenspaces can help reduce stress, anxiety and depressive symptoms (Sundara Rajoo et al, 2021). Furthermore, there is evidence that even brief outdoor experiences in green and blue spaces or having green window views during the strictest lockdown periods provide mental health benefits (Pouso et al, 2021; Soga, Evans, Tsuchiya, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…With this approach, findings that GI use are associated with better health can mean that the GI use has improved health, but these results could also represent a bias whereby those with poorer mental and physical health were less interested in using GI as a result of their health status. Three of the studies were able to more directly measure the impact of GI use by measuring individual outcomes before and after GI use [ 37 , 41 , 47 ], though they lacked controls to represent that effect of not using GI. While the high level of agreement across studies offers support for their conclusions on the benefits of GI use, studies with a random assignment of participants to control and use categories would be even stronger.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study reported changes in nature sound during the pandemic compared to pre-pandemic time (Garrido-Cumbrera et al, 2021) as a possible nature contact indicator. Other nature contact indicators including the quality of greenspace (Huerta & Utomo, 2021), nature experience activities (Jackson et al, 2021a), nature exercise and nature therapy (Sundara Keeren et al, 2021), and perceived nature deprivation (Tomasso et al, 2021) were reported in the literature.…”
Section: Contact With Naturementioning
confidence: 99%
“…Fifteen studies (25%), including 13 cross-sectional study designs (Asim et al, 2021;Basu et al, 2021;Bourion-Bédès et al, 2021a;Bu et al, 2021;Corley et al, 2021;Dzhambov et al, 2021;Heo et al, 2021;Lõhmus et al, 2021;Millán-Jiménez et al, 2021;Pouso et al, 2021;Sansal et al, 2021;Spano et al, 2021;Sundara Keeren et al, 2021), one cohort (Wortzel et al, 2021) and one longitudinal study design (Young et al, 2021) reported an association between the nature exposure and level of anxiety (Table 1). Of the total, five studies used the GAD-7 scale (Spitzer et al, 2006), three studies used GAD-2 (Kroenke et al, 2007), three used DASS-21 (Lovibond & Lovibond, 1995), one study used SCL-90 scale (Derogatis & Savitz, 1999), and the remaining three studies did not use any standard scale for assessing anxiety.…”
Section: Anxietymentioning
confidence: 99%
See 1 more Smart Citation